PERANCANGAN GELANGGANG OLAHRAGA DI DI DI KOTA SINGKAWANG - Karuniadi, Yoga Novian; Khaliesh, Hamdil; Nurhamsyah, Muhammad (JMARS: Jurnal Mosaik Arsitektur, 2025)
Indonesia is a country that has managed to improve the ranking of the Global Innovation Index in 2022, where this is influenced by the linkage of innovation and intangible assets through improving the quality of human resources. Singkawang City is one of the cities that has this potential in the province of West Kalimantan. Where this city as a whole has quite a high interest in sports and tourist activities, especially in the field of sports. However, so far Singkawang City does not have adequate sports facilities and infrastructure and can be used as a tourist destination. This indirectly requires many flexible architectural buildings so that they are not only built to fulfill a function of the building itself. Therefore, the need for a sports arena as a place to provide various kinds of sports facilities and at the same time become a flexible tourist destination. Departing from the needs and the problem gave an idea to the author in making a Design of a Sports Arena in Singkawang City with an iconic architectural approach. The design method used is the glass-box method as a form of effort to solve problems transparently. The result of the design is to be able to create a sports arena to meet the needs of sports facilities to improve the quality of human resources with an iconic and flexible design form in accommodating the needs of space use in the Singkawang City area.